Central System of Psychosocial Support to the Czech Victims Affected by the Tsunami in Southeast Asia - Vymetal, Stepan (Prehospital and disaster medicine, 2006)
The Tsunami disaster affected several countries in Southeast Asia in December 2004 and killed or affected many tourists, most of them from Europe. Eight Czech citizens died, and about 500 Czechs were seriously mentally traumatized. The psychosocial needs of tourists included: (1) protection; (2) treatment; (3) safety; (4) relief; (5) psychological first aid; (6) connecting with family members; (7) transportation home; (8) information about possible mental reactions to trauma; (9) information about the normality of their reaction; (10) procedural and environmental orientation; (11) reinforcement of personal competencies; and (12) psycho-trauma therapy. The Ministry of Foreign Affairs of the Czech Republic was in charge of general emergency management. General coordination of psychosocial support was coordinated under the Ministry of Interior of the Czech Republic, which is connected to the Central Crisis Staff of the Czech Government. The major cooperative partners were: the Ministry of Foreign Affairs, the Ministry of Defence, the Ministry of Health, Czech Airlines, psychosocial intervention teams of the Czech Republic, and the Czech Association of Clinical Psychologists. The main goals of relief workers were: (1) to bring back home the maximum number of Czech citizens; (2) to provide relevant information to the maximum number of affected Czech citizens; (3) to provide relevant information to rescue workers and professionals; and (4) to prepare working psychosocial support regional network. Major activities of the Ministry of Interior (psychology section) included: (1) establishing a psychological helpline; (2) running a team of psychological assistance (assistance in the Czech airports, psychological monitoring of tourists, crisis intervention, psychological first aid, assistance in the collection of DNA material from relatives); (3) drafting and distributing specific information materials (brochures, leaflets, address lists, printed and electronic instructions); (4) communicating via the media and advertising; and (5) providing analysis and research studies. Central coordination of psychosocial support has been found as successful in the first phase after the disaster. The plans must be built for preferable cooperation in the psychosocial field in the Czech Republic. Better collaborates with journalists must exist in order to reduce secondary psycho-trauma. There is a need for intensive international cooperation in the psychosocial field and to build the network at the global level.
Keywords: Asia, Southeastern; Tsunamis; jihovýchodní Asie; pomoc v nouzi; Crisis Intervention; Humans; Disasters; lidé; katastrofy; Relief Work; tsunami; krizová intervence